2015
DOI: 10.1039/c5ay02236c
|View full text |Cite
|
Sign up to set email alerts
|

A glassy carbon electrode based on graphene quantum dots (GQDs) for simultaneous detection of acetaminophen and ascorbic acid

Abstract: In this present work, graphene quantum dots (GQDs) were handily prepared with citric acid by the pyrolysis method and used to fabricate an electrochemical sensor for the simultaneous determination of acetaminophen (AC) and ascorbic acid (AA) in compound preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In addition, it can be concluded that the HNC-Rh-(ImS3-14) sensor presents good sensitivity and a low limit of detection in comparison to results recently published for similar studies ( Table 2). Given the fact that the sensor preparation is fast, easy and yields good analytical parameters, this represents a suitable method for paracetamol determination [25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it can be concluded that the HNC-Rh-(ImS3-14) sensor presents good sensitivity and a low limit of detection in comparison to results recently published for similar studies ( Table 2). Given the fact that the sensor preparation is fast, easy and yields good analytical parameters, this represents a suitable method for paracetamol determination [25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%